PENGARUH MORALITAS INDIVIDU, KOMITMEN ORGANISASI DAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN KECURANGAN (FRAUD) DALAM PENGELOLAAN KEUANGAN DESA - Ida Ayu Mega Evia Lestari; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2021)
Fraud prevention is an effort made to prevent someone from committing fraudulent acts that can cause losses. This study aims to determine the effect of individual morality, organizational commitment and a whistleblowing system on the prevention of fraud in village financial management. This research was conducted in all villages in the District of Mengwi. The sample in this study was 86 village officials. The sampling method used was proportionate stratified random sampling. The data analysis technique used in this research is descriptive statistics, validity test, reliability test, classical assumption test, multiple linear regression, coefficient of determination, F test, and t test. From the results of this study that the variables of individual morality, organizational commitment, whistleblowing system have a positive and significant effect on fraud prevention.